The morphological and physiological changes during the reproductive cycle of the female rock lizard, Agama atra Daudin, 1802 - Van Wyk, J. H. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 1982.